(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The purpose of this paper is to analyze the effect of education cost, university image and quality of lecturers on student decisions to choose a college. To achieve the proposed goals, a model is applied that reflects the effect of education costs, university image and quality of lecturers on student decisions to choose universities. This model was tested through the use of multiple linear regression equations and the sample was 388 student candidates. The conceptual model shows that the image of a university is the most influential construct on student decisions to choose a campus, followed by the quality of lecturers and the cost of education. In this paper, the cost of education variable produces a reliability of 0.861, a college image of 0.918 and a lecturer quality of 0.937. Further research is needed in order to find more reliable measurements of indicators of education cost, university image and quality of lecturers. The image of a university is the highest impression that is in the minds of students in choosing a university, followed by the quality of lecturers and the cost of education. Proven. The results show that the image of the university, the quality of the lecturers and the cost of education have an influence on student decisions to choose a campus.